Impact of central sensitization on pain intensity, pain-related symptoms, and health-related quality of life in chronic pain outpatient department - Deep Divanshu Lall; Rajat Gupta; Nandini Dadu; Ashu Jain (Indian Journal of Pain, 2021)
Context: Central sensitization (CS) has been proposed as a common underlying pathophysiology to explain poorly understood pain-related syndromes. This is termed under central sensitivity syndromes (CSSs), for which no specific organic cause has been found. Aims: The aim of the present study was to investigate whether there is an association between the CS Inventory (CSI) score, pain-related symptoms, pain-related disability, health-related quality of life (QOL), and poorly understood pain-related syndromes and whether they differed by disease type. This study also evaluated the association between severity of CS and the associated CSSs. Methods: A total of seventy patients who attended a pain clinic (chronic pain outpatient department) were assessed randomly. CSI score, CSSs, EuroQOL-5 Dimension-5 Level, Brief Pain Inventory, and Fibromyalgia (FM) Severity Scale were assessed and compared. Statistical Analysis: Univariate correlation analysis was performed in each group to evaluate: (1) severity of CS, (2) presence/absence of CSSs, (3) pain intensity and pain interference, and (4) CSI score and FM Severity Scale. Results: CSI score has a significant association with CSSs, pain-related symptoms such as pain/discomfort, anxiety/depression, mood, and sleep. Conclusions: In our study, CS has been shown to have a significant impact on mean pain score and QOL by strongly impacting mobility, mood, and sleep. CS is the underlying root cause of various CSSs. This study concludes that CS should be evaluated as a routine in all chronic pain patients.